Wear and corrosion behavior of nano carbide dispersed AISI304 stainless steel by laser surface processing. (10th December 2021) - Chakraborty, Amitesh; Dileep, M; Krishna, Shree; Pityana, Sisa; Sen, D; Manna, I; Majumdar, J Dutta
Abstract: In this study, dispersion of tungsten carbide on AISI 304 stainless steel substrate has been carried out by laser melting of the sand blasted substrate using a 5 kW continuous wave (CW) Nd:YAG laser (with the beam diameter of 3 mm) with an output power ranging from 1.5–2 kW, and scan speed varying from 12 to 16 mm s −1 and simultaneous feeding of premixed WC + Co powders in the ratio (wt) of 1:4 (with a flow rate of 10 mg s −1 ). The microstructure of the composite zone is dendritic or cellular in morphology and consists of nano-tungsten carbide (both WC and W2 C) and M23 C6 precipitates. There is an enhancement in hardness due to carbide dispersion from 220 VHN of the as-received substrate to 290–400 VHN. The wear resistance is improved significantly with a maximum enhancement observed in the sample processed with an applied power of 2 kW and a scan speed of 12 mm s −1 . The corrosion rate in a 3.56 wt% NaCl solution is significantly reduced due to laser processing in most samples except when processed with 2.5 kW applied power and 12 mm s −1 scan speed. However, pitting corrosion resistance is found to be improved (shifting of Epit towards noble direction) for the sample processed with an applied power of 2 kW and a scan speed of 12 mm s −1 .